Síntesis y caracterización de materiales absorbentes interpenetrados a partir de polímeros sensibles al pH y temperaturas. (2011)
Chitosan hydrogels cross-linked with dicarboxylic acids were prepared. Succinic, glutaric and adipic acid were used as cross-linking agents, the goal being to compare the effect of the length of the chain on the behavior of the material obtained. The swelling properties were studied at different pHs and temperatures, and it was discovered that these properties depend particularly on the pH of the environment. Creep-recovery and stress-relaxation studies were performed to determine mechanical properties and the chitosan/succinic acid hydrogels exhibited a completely viscous behavior. Thermal studies were carried out using differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA). DSC results revealed that the materials obtained are completely amorphous. Acetaminophen was used as a positive control for the release kinetics studies. Upon fitting the results to a specific mathematical model, it was determined that the release process is controlled by diffusion and relaxation of the polymer network.